Disseminated tuberculosis in HIV-infected patients from the Regional HIV/AIDS Center Constanţa, Romania - Rugină, Sorin (National Institute of Infectious Diseases “Prof. Dr. Matei Balş”, Romania, and the European Academy of HIV/AIDS and Infectious Diseases, 2014)
INTRODUCTION: The purpose of our study was to evaluate clinical and pathological characteristics as well as treatment outcomes in HIV-infected patients with disseminated tuberculosis from the Regional HIV/AIDS Center Constanţa, Romania, and to determine associated risk factors. METHODS: We analyzed HIV-infected adults diagnosed with disseminated tuberculosis (TB) over the past two years, monitored in the Regional HIV/AIDS Center Constanţa. RESULTS: Out of a total number of 956 HIV-infected patients, 42 had been diagnosed with tuberculosis over the past two years (2011-2013) (4.39%) and 16 of them developed disseminated TB (38%). At the time of diagnosis, we recorded abnormal chest X-rays in 8 (50%), and positive sputum cultures in 4 (25%) of them. The median CD4 count was 40 cells/μL with a range of 5-85 cells/μL; HIV-RNA was detectable in all cases. Multidrug-resistant tuberculosis (MDR-TB) was identified in 6 cases. The outcome was unfavorable in 15 patients. CONCLUSION: In our study, disseminated tuberculosis appeared to be a common pattern of evolution of HIV-TB co-infection (38%). Sputum smear positivity was low and chest X-ray images did not follow a typical pattern. HIV-TB co-infected patients with CD4 lymphocyte cell count <50 cells/μL were more likely to have disseminated TB. The severity of cases, proved by a high mortality rate, requires consideration of this diagnosis early in patients with advanced AIDS, even if laboratory investigations are not suggestive.